2017
DOI: 10.1111/jdv.14475
|View full text |Cite
|
Sign up to set email alerts
|

Acne prevalence and associations with lifestyle: a cross‐sectional online survey of adolescents/young adults in 7 European countries

Abstract: The overall prevalence of self-reported acne was high in adolescents/young adults in the European countries investigated. Heredity was the main risk factor for developing acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 42 publications
11
125
0
14
Order By: Relevance
“…While Capitanio et al . reported that tobacco smoking may have an impact on acne, two recent online surveys reported contradictory information with a protective effect on acne …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Capitanio et al . reported that tobacco smoking may have an impact on acne, two recent online surveys reported contradictory information with a protective effect on acne …”
Section: Resultsmentioning
confidence: 99%
“…While Capitanio et al reported that tobacco smoking may have an impact on acne, two recent online surveys reported contradictory information with a protective effect on acne. [92][93][94][95] Cigarette smoke (CS) is a highly complex aerosol composed of thousands of chemical substances, including nicotine, carbon monoxide, tar, formaldehyde, cyanhydric acid, ammonia, mercury, lead and cadmium. [96][97][98] These chemical substances from CS increase transepidermal water loss, degeneration of connective tissue in the skin and upregulation of matrix metalloproteinases 1 and 3 which degrade collagen and elastic fibres, and lastly impact on the natural skin barrier.…”
Section: Acne Exposome Factorsmentioning
confidence: 99%
“…The mean age of acne vulgaris among participants was 16 year old which is similar to findings documented in previous studies. For example, a Syrian study showed that the mean age of students with acne was significantly younger in males (18.13 ± 0.59) than in females (19.04 ± 1.10) [6], also among a total of 10 521 participants across 7 European countries the prevalence of acne was highest in the 15-to 17-year-old age class and decreased with increasing age [9]. Another huge study compared the epidemiology of acne vulgaris among Caucasian, Asian, Continental Indian and African American women showed that acne peaked between the ages of 16 and 20 years in all racial groups excluding Hispanic women, in whom acne peaked slightly later [7].…”
Section: Discussionmentioning
confidence: 99%
“…11 CSA Market Research Consultancy (Health Sector) recruited study participants by e-mail from a database of Internet users known to be willing to participate in surveys. 11 CSA Market Research Consultancy (Health Sector) recruited study participants by e-mail from a database of Internet users known to be willing to participate in surveys.…”
Section: Methodsmentioning
confidence: 99%